Bilateral Accessory C1 and C2 Facet Joints; Clinical, Neuroradiological and Peroperative Findings in an Adult with Quadriparesis - Chowdhury, Forhad H.; Haque, Mohammod Raziul; Hakim, Maliha; Arifin, Mohammod Shamsul; Islam, Soyed Ariful (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Objectives Accessory C1 and C2 facet joints are very rare. Only few cases were reported in the literature. We report a case of bilateral accessory facets in an adult with special attention to clinical, neuroradiological, as well as peroperative findings.Case report A 37-year-old male presented with progressive quadriparesis. Radiology revealed bilateral posterior accessory C1 and C2 facet joints compressing the spinal cord with craniovertebral junction (CVJ) instability. Both accessory C1 and C2 facets with the posterior arch of the C1 were removed. Lateral mass screws and plates fixation at the C1 and C2 level, as well as fusion, were performed. Postoperatively, the patient recovered well.Conclusion In accessory C1 and C2 facet joints, when symptomatic, neuroradiological findings can guide to the proper diagnosis, to pathological understanding, and, ultimately, to management strategy.
Keywords: accessory atlantoaxial facet joint; C1 and C2 accessory facets; craniovertebral junction; instability; quadriparesis; adult